(untitled) (E Global Congress, 2025)
Evaluation activities have been gradually developing in our republic since independence. Speaking about the positive experience of developing and applying in practice national state assessment standards that meet international requirements at the initial stages, it should be noted that at present there is no appropriate full-fledged regulatory framework, an effective management and control system that subordinates the activities of expert appraisers to certain procedures and rules. To study valuation, it is necessary first of all to have certain economic and technical knowledge, to know the content of the science of valuation, its formation and development as a separate science, the role of theoretical views and knowledge systems on the concept of property and property law, value, the value of property and their evaluation in these processes.